2022
DOI: 10.1080/08897077.2020.1728466
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Buprenorphine access for Veterans with Opioid use Disorder in Rural Clinics using Telemedicine

Abstract: Background: Having prescribers use clinical video teleconferencing (telemedicine) to prescribe buprenorphine to people with opioid use disorder (OUD) has shown promise but its implementation is challenging. We describe barriers, facilitators and lessons learned while implementing a system to remotely prescribe buprenorphine to Veterans in rural settings. Methods: We conducted a quality improvement project aimed at increasing the availability of medications for OUD (MOUD) to Veterans. This project focused on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 31 publications
1
50
0
1
Order By: Relevance
“…Technology-delivered care can be helpful in scaling interventions for rural adults with obesity residing in remote areas Policymakers can enhance reimbursement and incentives to promote telemedicine-delivered care to adults Enhancing patient/staff engagement and culture can overcome organizational stress and enhance reach of the intervention the Consolidated Framework for Implementation Research (CFIR) and RE-AIM [5]. These frameworks have previously been applied in the context of telemedicine and have found that patient and leadership engagement, comfort levels with the technology, and a need to have similar efficacy and workflows to in-person visits were important factors [6][7][8]. As such, the purpose of this analysis was to apply these established implementation frameworks to refine our intervention for a future, large-scale trial that could ensure its long-term success and program sustainability in rural areas.…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…Technology-delivered care can be helpful in scaling interventions for rural adults with obesity residing in remote areas Policymakers can enhance reimbursement and incentives to promote telemedicine-delivered care to adults Enhancing patient/staff engagement and culture can overcome organizational stress and enhance reach of the intervention the Consolidated Framework for Implementation Research (CFIR) and RE-AIM [5]. These frameworks have previously been applied in the context of telemedicine and have found that patient and leadership engagement, comfort levels with the technology, and a need to have similar efficacy and workflows to in-person visits were important factors [6][7][8]. As such, the purpose of this analysis was to apply these established implementation frameworks to refine our intervention for a future, large-scale trial that could ensure its long-term success and program sustainability in rural areas.…”
Section: Contributions To the Literaturementioning
confidence: 99%
“…10 Prescribing buprenorphine via telemedicine in nonrandomized studies appears to be safe and likely increases access in rural communities. 11 On March 6, 2020, the Centers for Medicare and Medicaid Services agreed to pay for telemedicine encounters during the COVID-19 public health emergency. 12 The Office for Civil Rights stipulated that providers who serve patients in good faith through everyday communication technologies, such as FaceTime or Skype, during the COVID-19 pandemic are protected from Health Insurance Portability and Accountability Act (HIPAA) enforcement.…”
mentioning
confidence: 99%
“…The results also indicated that participants in this study were statistically significantly less satisfied with their health during the compulsory stay-at-home order in Alaska as compared to prior to the compulsory stay-at-home order. Telemedicine for veterans in the US has increased in recent years for a variety of health services, including sleep (e.g., Sarmiento et al, 2019), drug use (e.g., Brunet et al, 2020), and PTSD (e.g., Campbell et al, 2020). Additional telemedicine services for veterans have also emerged as a result of the COVID-19 pandemic, including, for example, an increase in behavioral health telemedicine (e.g., Shelton et al, 2020); however, additional research has noted the need for even more telemedicine services during the COVID-19 pandemic (Egede et al, 2020).…”
Section: Discussionmentioning
confidence: 99%